A parallel numerical algorithm by combining MPI and OpenMP programming models with applications in gravity field recovery - Lu, Biao; Luo, Zhicai; Zhong, Bo; Zhou, Hao (Frontiers in Earth Science, 2023)
Satellite gravimetry missions have enabled the calculation of high-accuracy and high-resolution Earth gravity field models from satellite-to-satellite tracking data and gravitational gradients. However, calculating high maximum degree/order (e.g., 240 or even higher) gravity field models using the least squares method is time-consuming due to the vast amount of gravimetry observations. To improve calculation efficiency, a parallel algorithm has been developed by combining Message Passing Interface (MPI) and Open Multi-Processing (OpenMP) programming models to calculate and invert normal equations for the Earth gravity field recovery. The symmetrical feature of normal equations has been implemented to speed up the calculation progress and reduce computation time. For example, the computation time to generate the normal equation of an IGGT_R1 test version of degree/order 240 was reduced from 88 hours to 27 hours by considering the symmetrical feature. Here, the calculation was based on the high-performance computing cluster with 108 cores in the School of Geodesy and Geomatics, at Wuhan University. Additionally, the MPI parallel Gaussian-Jordan elimination method was modified to invert normal equation matrices and scaled up to 100 processor cores in this study while the traditional method was limited in a certain number of processors. Furthermore, the Cholesky decomposition from the ScaLAPACK library was used to compare with the parallel Gauss-Jordan elimination method. The numerical algorithm has effectively reduced the amount of calculation and sped up the calculation progress, and has been successfully implemented in applications such as building the gravity field models IGGT_R1 and IGGT_R1C.